A 27-Year Retrospective Study of Pediatric Suicide Cases Referred to the Medical University of South Carolina (1988-2014). Issue 3 (September 2016) - Singh, Balvir; Schandl, Cynthia A.; Tormos, Lee M.
Suicide by individuals under 18 years of age is a tragic reality of society. To assess local trends and demographics, we retrospectively reviewed all pediatric cases referred to our institution from 1988-2014 (27 years). Pediatric cases were defined as individuals younger than 18 years of age. The incidence of reported suicides declined from 3.8 cases per year to 2.4 cases per year as compared to observations at our institution over a previous ten-year period (1988-1998). In concert with the overall decrease in cases were increases in the proportion of adolescents younger than 15 and the female demographic. Furthermore, a shift in suicidal methodology was noted, with an increase in suicide by hanging. Indeed, for females, hanging became the most common suicide modality, replacing firearms. Our findings are congruent with national trends and underline the need for global suicide preventive interventions targeted toward increasingly younger adolescents and females.